Bacteriophage therapy in aquaculture: current status and future challenges - Liu, Ruyin; Han, Ganghua; Li, Zong; Cun, Shujuan; Hao, Bin; Zhang, Jianping; Liu, Xinchun (Folia microbiologica, 2022)
The escalation of antibiotic resistance has revitalized bacteriophage (phage) therapy. Recently, phage therapy has been gradually applied in medicine, agriculture, food, and environmental fields due to its distinctive features of high efficiency, specificity, and environmental friendliness compared to antibiotics. Likewise, phage therapy also holds great promise in controlling pathogenic bacteria in aquaculture. The application of phage therapy instead of antibiotics to eliminate pathogenic bacteria such as Vibrio, Pseudomonas, Aeromonas, and Flavobacterium and to reduce fish mortality in aquaculture has been frequently reported. In this context, the present review summarizes and analyzes the current status of phage therapy in aquaculture, focusing on the key parameters of phage application, such as phage isolation, selection, dosage, and administration modes, and introducing the strategies and methods to boost efficacy and restrain the emergence of resistance. In addition, we discussed the human safety, environmental friendliness, and techno-economic practicability of phage therapy in aquaculture. Finally, this review outlines the current challenges of phage therapy application in aquaculture from the perspectives of phage resistance, phage-mediated resistance gene transfer, and effects on the host immune system.
Keywords: Animals; antibakteriální látky; Anti-Bacterial Agents; Vibrio; bakteriofágy; Aquaculture; fágová terapie; Bacteriophages; Phage Therapy; vodní hospodářství; zvířata